Du patrimoine au Liban-Sud : le château de Šaqyf/Beaufort, entre ressources et conflits - Zara Fournier (Les Cahiers d’EMAM)
This article queries the staging of places in South-Lebanon, a region fluctuating between conflicts and post-conflicts, by focusing on the example of the commonly named “Šaqyf Castle/Beaufort Castle”. After 18 years of occupation by the Israeli army, the ruins of this fort have been the object of an important rehabilitation project led by the Ministry of Culture that aimed not only at staging its history but also at building a tool to go beyond the conflict. But the power struggles amongst the project stake holders and the multiple images and narratives produced around the castle show that the heritage project is a tool used to stage competitive belongings and identifications to the place, in a fluctuant context. Calling Šaqyf/Beaufort a “heritage” is then a way to silence the concurrent memories and claims for the place. Heritage is then, is a post-conflict situation, a mean to perpetuate the conflict.